Protective effect of flavonoids from Passiflora edulis Sims on diabetic complications in rats - Salles, Bruno César Correa; Leme, Krissia Caroline; da Silva, Marcelo Aparecido; da Rocha, Cláudia Quintino; Tangerina, Marcelo M P [UNESP]; Vilegas, Wagner [UNESP]; Figueiredo, Sônia A; Duarte, Stella Maris da Silveira; Rodrigues, Maria Rita; de Araújo Paula, Fernanda Borges (Oxford University Press (OUP), 2021)
OBJECTIVES: This study was carried out to evaluate the effects of flavonoids present in leaves of Passiflora edulis fruit on complications induced by diabetes in rats. METHODS: The extract of P. edulis leaf was obtained by 70% ethanol maceration. From the dry extract, the fractions were obtained by consecutive liquid-liquid partition with hexane, ethyl acetate and n-butanol. The content of isoorientin of ethyl acetate and n-butanol fractions was determined by ultra-performance liquid chromatography coupled with electrospray and triple quadrupole ionization (TQD) analysis in tandem mass spectrometry (UPLC-ESI-Tq-MS). Only Fr-BuOH was used to treat diabetic or not Wistar rats. Biochemical parameters, platelet aggregation and production of reactive species were evaluated. KEY FINDINGS: The UPLC-ESI-Tq-MS analysis revealed the presence of several flavonoids, among which we identified five possible flavonoids c-heterosides (luteolin-7-O-pyranosyl-3-O-glucoside, apigenin-6-8-di-C-glycoside, apigenin-6-C-arabinoside-8-C-glycoside, isoorientin, isovitexin). The diabetic rats (treated intraperitoneally with alloxan, 150 mg/kg) treated with Fr-BuOH (20 mg/kg/day for 90 days) presented improvement in blood glucose, serum levels of fructosamine, lipid profile and urea. Furthermore, the Fr-BuOH reduced both platelet aggregation and the production of oxidant species in diabetic animals. CONCLUSIONS: These results suggested that flavonoid C-glycosides present in the Fr-BuOH may be beneficial for the diabetic state, preventing complications induced by diabetes.
Keywords: Passiflora edulis; antiplatelet; diabetes; isoorientin; LC-MS quantification